CUMULATIVE GENERAL LEDGER THE TOBACCO INSTITUTE INC PERIOD ENDING 19891231 (Tufts Archival Research Center, 2007)
Marginalia; Cumulative general ledger for the Tobacco Institute for the period ending 12/31/89. Summarizes the debt for various vendors. Lists the check number, the debt owed, the credit issued for each vendor and the closing balance.